Passenger flows in CGE models for transport project evaluation - Johannes Bröcker (European Regional Science Association (ERSA), 2002)
Recently computable general equilibrium methods are becoming more and more popular for estimating welfare effects of transport projects, when a differentiation by region or social group is required. This paper focuses on the spatial distributional dimension. Most spatial CGE applications, however, have up to now only taken the impact of goods transport costs into consideration. To a large extent, however, welfare effects are due to time and cost savings in passenger transport. This paper extends the CGE approach by including private passenger transport. It aims at a model design deriving passenger flows from individual optimising behaviour; it uses parsimonious functional forms such that it is possible to calibrate the model using benchmark data on O-D passenger flows and willingness to pay estimates for time savings. The latter will be borrowed from the literature. The paper will present different specifications: with and without an explicit time constraint; continuous and discrete decisions on the level of the individual. Equivalent variation measures for quantifying welfare impacts in monetary terms will be derived.
Keywords: 330